ANALISIS PENDAPATAN USAHA PENGOLAHAN PISANG RIMPI (Musa brachycarpa Back) DI DESA TUNGKAP KECAMATAN BINUANG KABUPATEN TAPIN PROVINSI KALIMANTAN SELATAN - Wasdiyanta; Yayuk Minta Wahyuningsih; Zuraida (Fakultas Pertanian UVAYA Banjarmasin, 2025)
One of the food crop commodities that is able to support the establishment of several industries is bananas. The aim of this research is to determine the manufacturing process, revenue costs and income of the rimpi banana business in Tbesar Village. The research method used is a case study method of traditional business implementation through the fumigation process. The production of making Rimpi bananas for 1 month is 1,050 kg. The total variable is IDR. 13,327,188,199, total receipts of Rp. 21,000,000/month, so the income obtained from the banana rimpi business is Rp. 7,672,811,801/month